Oedometric compression of a granular material: computation of energies involved during breakage with a discrete element modelling - Nader François; Silvani Claire; Djeran-Maigre Irini (EPJ Web of Conferences, 2021)
A numerical model able to simulate the grain breakage with the discrete element method, using the “Non-Smooth Contact Dynamics” is presented. The model reproduces 3D grains having complex shapes and is tested in single grain and in oedometric compressions. Numerical simulations are then carried out to evaluate the different energies active during breakage (surface creation and redistribution energies). The surface creation energy is estimated. Results are closed to the ones found in the literature.